An annotated checklist of click-beetles (Coleoptera, Elateridae) from Iran - Platia, Giuseppe; Ghahari, Hassan (Zootaxa, 2016)
The fauna of Iranian Elateridae (Coleoptera: Elateroidea) is summarized in this paper. In total 245 species from 58 genera and 7 subfamilies Agrypninae Candèze (13 genera, 36 species), Cardiophorinae Candèze (4 genera, 55 species), Cebrioninae Latreille (2 genera, 6 species), Dendrometrinae Gistel (13 genera, 28 species), Elaterinae Leach (23 genera, 104 species), Lissominae Laporte (1 genus, 1 species) and Negastriinae Nakane & Kishii (2 genera, 15 species) are listed in literature as the fauna of Iran. Totally 74 species are endemic to Iran.